Percutaneous left atrial appendage closure with the Watchman device: a systematic review - Maksym, Jakub; Grabowski, Marcin; Mazurek, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2024)
Atrial fibrillation (AF) is the most commonly observed arrhythmia in the world and its prevalence increases with age. The main and most severe complication of AF is ischemic stroke. Oral anticoagulation (OAC) therapy is the standard of care for stroke prevention in the high risk population. Initiation of this treatment is associated with a substantial risk of bleeding complications. Moreover, there is a group of patients who cannot tolerate OAC. In patients with AF the left atrial appendage (LAA) is the main source of thrombus formation. Percutaneous left atrial appendage closure (LAAC) has become an important non-pharmacological intervention for stroke prevention in patients with non-valvular AF. The procedure aims to reduce the risk of thromboembolism without increasing the risk of bleeding. Over the last few years, the safety and long-term efficacy of the procedure in specific populations have increased and more patients are being treated. The Watchman device is the most studied device in this field. Randomized controlled trials demonstrated non-inferiority of percutaneous left atrial appendage closure using the WATCHMAN 2.5 device to OAC (Boston Scientific, Marlborough, MA, USA). The new generation device, WATCHMAN FLX, was introduced and its use was associated with fewer safety events and a higher success rate of effective appendage closure. Nevertheless, several unsolved problems remain, including device-related thrombosis, the post-LAAC antithrombotic regimen, and peri-device leakage. This review will focus on LAAC with the Watchman device for stroke prevention in AF patients. Current status, available literature, clinical safety and efficacy will be summarized.